Integrative metabolomic and transcriptomic reveals potential mechanism for promotion of ginsenoside synthesis in Panax ginseng leaves under different light intensities - Di, Ping; Yang, Xiao; Wan, Mingming; Han, Mei; Zhang, Yonggang; Yang, Limin (Frontiers in Bioengineering and Biotechnology, 2023)
Panax ginseng C.A. Meyer is a shade plant, and its leaves are an important medicinal part of P. ginseng. Light intensity plays a crucial role in physiological activities and metabolite accumulation in P. ginseng. Currently, little is known about the molecular mechanisms underlying physiological changes and quality under different light intensities in P. ginseng leaves. Therefore, we investigated the changes in photosynthetic physiology, secondary metabolism, transcriptomics, and metabolomics of P. ginseng leaves under different light intensities [T20 (20 µmol m-2·s-1), T50 (50 µmol m-2·s−1), T100 (100 μmol m−2·s−1)]]. Higher light intensity positively influenced the yield, photosynthesis, and accumulation of polysaccharides, soluble sugars, terpenoids, and ginsenosides in P. ginseng leaves. The T100 treatment notably promoted the accumulation of ginsenosides in the leaves, resulting in a 68.32% and 45.55% increase in total ginsenosides compared to the T20 and T50 treatments, respectively. Ginsenosides Rg1, Re, Rb1, Rc, Rg2, Rb2, Rb3, and Rd were 1.28-, 1.47-, 2.32-, 1.64-, 1.28-, 2.59-, 1.66-, and 2.28-times higher than in the T20 treatment. Furthermore, 285 differentially accumulated metabolites (DAMs) and 4218 differentially expressed genes (DEGs) in the metabolome and transcriptome of P. ginseng leaves, respectively, were identified. 13 triterpenoid saponins were significantly upregulated, and three were downregulated. The expression of genes encoding photosystem II reaction center proteins was upregulated under the T100 treatment, thereby increasing photosynthetic activity. The T100 treatment enhanced the expression of genes involved in photosynthetic carbon and energy metabolism in P. ginseng. The expression of antenna protein synthesis genes was upregulated under the T20, which increased the ability to capture light in P. ginseng leaves. T100 upregulated the expression of HMGR, SS, CYP716A53v2, UGT74AE, PgUGT1, and UGTPg45, thereby promoting terpene and ginsenoside synthesis. In summary, 100 µmol m−2·s−1 was conducive to quality formation of P. ginseng leaves. This study elucidates molecular mechanisms underlying the photosynthetic physiology and ginsenoside synthesis in P. ginseng under varying light intensities and provides a theoretical basis for the P. ginseng cultivation and its industrial production of secondary metabolites.